Violence, Adolescence, and Canadian Religious Communities: A Quantitative Study - Michaelson, Valerie (Journal of interpersonal violence, 2021)
Exposure to violence is recognized as a major health concern among adolescent populations. The evidence base that links religious involvement with risks for child violence is inconsistent. In a national analysis involving a weighted sample of 24,307 young people, we studied the perpetration of violence (fighting and bullying), as well as victimization by violence (bullying only), among young people who were affiliated with religious groups. One in four young Canadians reported involvement in such groups. Study findings confirmed some unique patterns among this group. First, these religiously involved children reported the same or greater levels of perpetration of violence than other children. Second, religiously involved children reported the same or greater levels of experiencing victimization from violence. Third, religious involvement appeared to protect against engagement in certain overt risk-taking behaviors, but not violence. These patterns were consistent even after adjustment for family, community, socioeconomic, and school-related determinants. If religious communities are to fulfill mandates that foster the protection and nurturing of children into healthy relationships, violence is best addressed using evidence-based strategies. Development of such effective preventive strategies requires the incorporation of contemporary evidence about the distribution, determinants, and possible effects of violence in such groups. Findings from our study suggest that a silence around the issue of violence may in fact be true in the context of some Canadian religious communities. Yet, if these communities make an intentional commitment to protecting children from violence and promoting healthy relationships, and are willing to learn from evidence-based practices that have shown to protect children from participating in and experiencing violent and victim behaviors, perhaps these disturbing trends could be reversed. This message is germane for all levels of leadership in Canadian religious communities.